(untitled) (Innovaciones Educativas, 2022)
Difficulties related to calculus teaching and learning involve both the students taking class and the teachers in charge, particularly when curricular changes force teachers to teach calculus at high school level. In that sense, this work’s objective was to inquire what teachers know about the calculus concepts of limit, derivative, and integral. In order to do that, we used the analytical model of Mathematics Teacher’s Specialized Knowledge, known as MTSK. Using a qualitative methodology, we applied a test to Math teachers in Chile, addressing their analysis of the category definition, properties, and foundations of the subdomain of knowledge on the subject. The primary outcomes show the tendency to teach these topics using a traditional approach, emphasizing scholarly definition and some dynamic geometry contributions for conceptual visualization. This study intends to contribute to the understanding of mathematics teachers’ knowledge, evidencing how they face the teaching of calculus in secondary school in the new curricular scenario in Chile. Moreover, it promotes reflection not only on the knowledge that they need to teach the mathematical limit, derivative and integral objects but also about their role in treating calculus issues for secondary education.